Forever Chemicals Needing Immediate Solutions: Mainers’ Preferences for Addressing PFAS Contamination - Zimmerman, Charity; Noblet, Caroline; Shea, Molly (Maine Policy Review, 2022)
Per- and poly-fluoroalkyl substances (PFAS) are a diverse class of synthetic fluorinated chemicals also referred to as “forever chemicals.” The release of these chemicals into the environment presents an urgent, emerging threat to human and environmental health. Decision-makers seeking to address a variety of PFAS-related issues need better understanding of citizens’ knowledge of PFAS contamination and their preferences for managing the issue. To provide this vital information, we analyze data from a survey of Maine citizens. We assess Maine residents’ baseline knowledge of PFAS contamination, as well as their preferences for generation and allocation of funds to address PFAS contamination in Maine. Per- and poly-fluoroalkyl substances (PFAS) are a diverse class of synthetic fluorinated chemicals also referred to as “forever chemicals.” The release of these chemicals into the environment presents an urgent, emerging threat to human and environmental health. Decision-makers seeking to address a variety of PFAS-related issues need better understanding of citizens’ knowledge of PFAS contamination and their preferences for managing the issue. To provide this vital information, we analyze data from a survey of Maine citizens. We assess Maine residents’ baseline knowledge of PFAS contamination, as well as their preferences for generation and allocation of funds to address PFAS contamination in Maine.